2015
DOI: 10.1186/s12875-015-0227-8
|View full text |Cite
|
Sign up to set email alerts
|

General practitioners’ perceptions on home medicines reviews: a qualitative analysis

Abstract: BackgroundHome Medicines Review (HMR) is an Australian initiative introduced in 2001 to improve quality use of medicines. Medication management services such as HMRs have the potential to reduce medication related problems. In 2011, changes to the HMR program were introduced to allow for referrals directly to accredited pharmacists in addition to the community pharmacy referral model. These changes were introduced to improve efficiency of the process. This study explored the perceptions of Western Australian g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 12 publications
1
30
0
1
Order By: Relevance
“…There is a low HMR participation rate from GPs and a poor awareness among patients. 14,[17][18][19][20][21] Low GP participation has been reported to relate to the cumbersome consent, referral and implementation processes, and inconsistent quality of service provided by pharmacists. 18,19 Attempts to increase HMR uptake, including for home nursing clients, have been unsuccessful.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
“…There is a low HMR participation rate from GPs and a poor awareness among patients. 14,[17][18][19][20][21] Low GP participation has been reported to relate to the cumbersome consent, referral and implementation processes, and inconsistent quality of service provided by pharmacists. 18,19 Attempts to increase HMR uptake, including for home nursing clients, have been unsuccessful.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
“…Furthermore, there have been concerns over the retail context of community pharmacies introducing structural and organisational barriers to integration between community pharmacies and GP practices (Jacobs et al., ; Royal Pharmaceutical Society, ). Consequently, pharmacists have been sceptical towards role expansion (Anderson, Blenkinsopp, & Armstrong, ; Eades et al., ; Hall, Donovan, & Wilkes, ) and GPs have been reluctant to accept extended services despite their potential to reduce their pressure and workload (Dhillon, Hattingh, Stafford, & Hoti, ; Hossain et al., ; McGrath et al., ; Smith, Cannon‐Breland, & Spiggle, ).…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, approximately one‐half of the QD identified in the present study overlapped with barriers and facilitators to home pharmacy service provision identified in different countries, specifically, Australia, Canada, UK and USA . However, some QD specifically related to HPC (i.e.…”
Section: Discussionmentioning
confidence: 64%
“…Not surprisingly, approximately one-half of the QD identified in the present study overlapped with barriers and facilitators to home pharmacy service provision identified in different countries, specifically, Australia, Canada, UK and USA. [21][22][23][24] However, some QD specifically related to HPC (i.e. working policy, collaborative visiting schedule arrangement, non-professional services, timeliness of sharing information, grief care, withdrawal of the service).…”
Section: Discussionmentioning
confidence: 99%